Zasada dobra wspólnego a demokracja. Próba analizy stanowiska J. Maritaina - Turek, Joanna (Annales. Etyka w Życiu Gospodarczym, 2008)
In the following paper the author presents and analyses J. Maritain’s social theory. The French Thomist attempted to associate the principle of common good (that plays the main role in the Christian social thought) with democracy. Maritain claims that only democracy can be regarded as an acceptable form of government, i.e. the one that satisfies rational and moral requirements (which, according to the Thomists, are the same). Such a statement put forward by the Thomist philosopher emphasises the necessity of asking a number of questions of the human nature, human dignity and human autonomy; it also demonstrate how to introduce the ethical values into the realm of democratic politics, which in its turn is described as axiologically neutral by contemporary political theories. J. Maritain’s views on those issues were taken into consideration by Catholic intellectuals and were announced before the Second Vatican Council. Regarding the time they were widely opened to the contemporary ideas. Consequently, they contributed to the significant development of the current attitude of the Catholic Church to the present political and social problems.